Comprehensive molecular profiling of sarcomas in adolescent and young adult patients: Results of the EORTC SPECTA-AYA international proof-of-concept study. (January 2023) - Morfouace, Marie; Horak, Peter; Kreutzfeldt, Simon; Stevovic, Aleksandra; de Rojas, Teresa; Denisova, Evgeniya; Hutter, Barbara; Bautista, Francisco; Oliveira, Júlio; Defachelles, Anne-Sophie; White, Jeff; Kasper, Bernd; et al.
Abstract: Background: Adolescent and young adult (AYA) patients with cancer are poorly recruited to molecularly targeted trials and have not witnessed the advances in cancer treatment and survival seen in other age groups. We report here a pan-European proof-of-concept study to identify actionable alterations in some of the worst prognosis AYA cancers: bone and soft tissue sarcomas. Design: Patients aged 12–29 years with newly diagnosed or recurrent, intermediate or high-grade bone and soft tissue sarcomas were recruited from six European countries. Pathological diagnoses were centrally reviewed. Formalin-fixed tissues were analysed by whole exome sequencing, methylation profiling and RNA sequencing and were discussed in a multidisciplinary, international molecular tumour board. Results: Of 71 patients recruited, 48 (median 20 years, range 12–28) met eligibility criteria. Central pathological review confirmed, modified and re-classified the diagnosis in 41, 3, and 4 cases, respectively. Median turnaround time to discussion at molecular tumour board was 8.4 weeks. whole exome sequencing (n = 48), methylation profiling (n = 44, 85%) and RNA sequencing (n = 24, 50%) led to therapeutic recommendations for 81% patients, including 4 with germ line alterations. The most common were for agents targeted towards tyrosine kinases (n = 20 recommendations), DNA repair (n = 18) and the PI3K/mTOR/AKT pathway (n = 15). Recommendations were generally based on weak evidence such as activity in a different tumour type (n = 68, 61%), reflecting the dearth of relevant molecular clinical trial data in the same tumour type. Conclusions: We demonstrate here that comprehensive molecular profiling of AYA patients' samples is feasible and deliverable in a European programme. Highlights: AYA cancers have been neglected by molecular profiling initiatives. Most AYA sarcomas of adequate sample quality have identifiable actionable mutations. Clinical evidence to support personalised treatment for AYAs is weak or absent. International molecular profiling is feasible and necessary to fill research gaps. More effort is needed to enable AYA patients' access to molecularly focused trials.